Rose hip: a potential future crop for processing and value-addition - Singh, Desh Beer; Lal, Shiv (Indian Horticulture, 2019)
Roses are a group of herbaceous shrubs belonging to family Rosaceae and found in temperate regions throughout both hemispheres. There are over 100 species of Rose, whereas, Rosa canina is used especially for its rose hips. The genus, Rosa, is derived from the Greek, roden, meaning â€œredâ€ and the Latin, ruber, also meaning â€œrubyâ€ or â€œredâ€, as apparently, the Roses of the ancient Mediterranean region were deep crimson, giving birth to legend that flowers sprang from the blood of Adonis. There are now hundreds of species of this beautiful flower cultivated throughout the world that occupy a vital place in medicine, as well as cosmetics, perfumes, soaps, and foods. Rose hips contain many vitamins and other beneficial supplements including lycopene, essential fatty acids, Î²-carotene, bioflavonoids and many essential minerals. They also contain highest concentration of vitamin C. Rose hips are used to prepare teas, extracts, purees or marmalades. They are also often dried. Dried rose hip fruits were used in folk medicines for digestive problems, urinary tract and kidney disorders, rheumatism, gout, colds and febrile conditions.